More stately mansions (New York : Artcraft Lithograph & Printing Co., 1967)
Poster for "More Stately Mansions" shows Ingrid Bergman, Arthur Hill, and Colleen Dewhurst in a scene from the play.
Title from item.
Artcraft Poster Collection (Library of Congress).
Keywords: Theatrical posters -- American -- 1960-1970.; Lithographs -- Color -- 1960-1970.